Dual PI3K/mTOR inhibitor NVP-BEZ235 decreases the proliferation of doxorubicin-resistant K562 cells - Li, Jie (Mol Med Rep, 2021)
Acute myelogenous leukemia (AML) is frequently accompanied by a poor prognosis. The majority of patients with AML will experience recurrence due to multiple drug resistance. Our previous study reported that targeting the mTOR pathway may increase cell sensitivity to doxorubicin (Doxo) and provide an improved therapeutic approach to leukemia. However, the effect and mechanism of action of NVP-BEZ235 (BEZ235), a dual inhibitor of PI3K/mTOR, on Doxo-resistant K562 cells (K562/A) is yet to be elucidated. Therefore, the aim of the present study was to investigate the effects of BEZ235 on K562/A cell proliferation. K562/A cells was investigated using CCK-8, flow cytometry and western blotting, following BEZ235 treatment. It was observed that BEZ235 significantly decreased the viability of K562/A cells. In addition, BEZ235 arrested K562/A cells at the G(0)/G(1) phase, and reduced the protein expression levels of CDK4, CDK6 and cyclin D1. Apoptotic cells were more frequently detected in K562/A cells treated with BEZ235 compared with the control group (12.97±0.91% vs. 7.37±0.42%, respectively; P<0.05). Cells treated with BEZ235 exhibited downregulation of Bcl-2 and upregulation of Bax. Furthermore, BEZ235 treatment markedly decreased the activation of the PI3K/AKT/mTOR pathway and its downstream effectors. Thus, these results demonstrated that BEZ235 inhibited cell viability, induced G(0)/G(1) arrest and increased apoptosis in K562/A cells, suggesting that BEZ235 may reverse Doxo resistance in leukemia cells. Therefore, targeting the PI3K/mTOR pathway may be of value as a novel therapeutic approach to leukemia.